2001
DOI: 10.4038/jnsfsr.v29i1-2.2621
|View full text |Cite
|
Sign up to set email alerts
|

Some physico-chemical characters of groundwater in some (selected) water supply wells in the Jaffna peninsula

Abstract: Abstract:The study focussed on the criteria used in assessing the quality of ground water. Among physical properties, turbidity, colour, odour and taste and among chemical properties; chloride, iron and sulphate concentration, total alkalinity, total dissolved solids, electrical conductivity and pH were determined for seven water supply wells. These values were compared with WHO standards and Sri Lankan standard values. Water supply wells a t Velanai and Chunnakam did not have quality problems and can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The porous limestone geology of aquifers is recharged directly by rainfall, which percolates through the fissures and floats as mound-shaped lenses on top of a denser layer of seawater. Significant imbalance has been noted between the draw-off and recharge rate and several studies have reported higher electrical conductivity (EC) values in the groundwater of the Jaffna peninsula [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The porous limestone geology of aquifers is recharged directly by rainfall, which percolates through the fissures and floats as mound-shaped lenses on top of a denser layer of seawater. Significant imbalance has been noted between the draw-off and recharge rate and several studies have reported higher electrical conductivity (EC) values in the groundwater of the Jaffna peninsula [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, documentation on the long-term effects of salinity on coastal paddy fields remains limited. Most of the coastal studies that have researched and examined water quality parameters, including salinity levels in groundwater systems in the area, have focused on a specific period [30] or short term [27,[31][32][33], the longest period being a one year trend [23,26,34]. This present study is aimed at investigating the spatial and temporal changes in groundwater salinity of Jaffna Peninsula over the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Here again the high levels of nitrate in well waters were attributed to the leached nitrogen fertilizers used in the intensive agriculture practised in the peninsula. Nanthini et al (2001) studied the physico-chemical characteristics of groundwater in some selected water supply wells in the Jaffna Peninsula. The study was mainly directed towards assessing the water for human consumption with respect to colour, turbidity, chloride, iron, sulphites, pH and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly half of the population (Nanthini et al, 2001) in Jaffna peninsula depends with tube well water or dug well water for their drinking purposes. The average annual groundwater recharge was 569,624 m 3 from April 2007 to March 2008 and the average annual groundwater withdrawal was 661,635 m 3 resulting a negative water balance of 92,011 m 3 (Nanthini et al, 2001). There is an imbalance between extraction and recharge of groundwater.…”
Section: Groundwater Usage In Jaffna Peninsulamentioning
confidence: 99%
“…It is necessary to monitor the quantity and quality of water stored and extracted from these aquifers (Mikunthan et al, 2013). Due to intensive domestic usage (250 L/day per capita), higher inorganic fertilizer use, resettlement and urbanization deteriorate water quality (Nanthini et al, 2001). There should be a monitoring system in the water management to assist long term planning of water supply in Jaffna peninsula.…”
Section: Introductionmentioning
confidence: 99%